Laparoscopic Versus Open Gastrectomy for Gastric Cancer (LOGICA): A Multicenter Randomized Clinical Trial. Issue 9 (20th March 2021) - van der Veen, Arjen; Brenkman, Hylke J. F.; Seesing, Maarten F. J.; Haverkamp, Leonie; Luyer, Misha D. P.; Nieuwenhuijzen, Grard A. P.; Stoot, Jan H. M. B.; Tegels, Juul J. W.; Wijnhoven, Bas P. L.; Lagarde, Sjoerd M.; de Steur, Wobbe O.; Hartgrink, Henk H.; et al.
Abstract : BACKGROUND: The oncological efficacy and safety of laparoscopic gastrectomy are under debate for the Western population with predominantly advanced gastric cancer undergoing multimodality treatment. METHODS: In 10 experienced upper GI centers in the Netherlands, patients with resectable (cT1-4aN0-3bM0) gastric adenocarcinoma were randomly assigned to either laparoscopic or open gastrectomy. No masking was performed. The primary outcome was hospital stay. Analyses were performed by intention to treat. It was hypothesized that laparoscopic gastrectomy leads to shorter hospital stay, less postoperative complications, and equal oncological outcomes. RESULTS: Between 2015 and 2018, a total of 227 patients were randomly assigned to laparoscopic (n = 115) or open gastrectomy (n = 112). Preoperative chemotherapy was administered to 77 patients (67%) in the laparoscopic group and 87 patients (78%) in the open group. Median hospital stay was 7 days (interquartile range, 5-9) in both groups ( P = .34). Median blood loss was less in the laparoscopic group (150 v 300 mL, P < .001), whereas mean operating time was longer (216 v 182 minutes, P < .001). Both groups did not differ regarding postoperative complications (44% v 42%, P = .91), in-hospital mortality (4% v 7%, P = .40), 30-day readmission rate (9.6% v 9.1%, P = 1.00), R0 resection rate (95% v 95%, P = 1.00), median lymph node yield (29 v 29 nodes, P = .49), 1-year overall survival (76% v 78%, P = .74), and global health-related quality of life up to 1 year postoperatively (mean differences between + 1.5 and + 3.6 on a 1-100 scale; 95% CIs include zero). CONCLUSION: Laparoscopic gastrectomy did not lead to a shorter hospital stay in this Western multicenter randomized trial of patients with predominantly advanced gastric cancer. Postoperative complications and oncological efficacy did not differ between laparoscopic gastrectomy and open gastrectomy.